Advancing the application of omics‐based biomarkers in environmental epidemiology. (21st March 2013) - Vineis, Paolo; van, Karin; Chadeau‐Hyam, Marc; Athersuch, Toby J.
<x xml:space="preserve">Abstract</x> The use of omics represents a shift in approach for environmental epidemiology and exposure science. In this article, the aspects of the use of omics that will require further development in the near future are discussed, including (a) the underlying causal interpretation and models; (b) the "meet‐in‐the‐middle" concept, with examples; (c) the role of "calibration" of measurements; and (d) the role of life‐course epidemiology and the related development of adequate biostatistical models. Environ. Mol. Mutagen. 54:461‐467, 2013. © 2013 Wiley Periodicals, Inc.